Analisis Perbandingan Pengaruh Penggunaan Flyslab dan Plat Floordeck dalam Mewujudkan Lean Construction - Sandagie, Edwin; Wibowo, M. Agung; Purwanggono, Bambang (Department of Civil Engineering, Diponegoro University, 2016)
Nowadays there are several kinds of products innovations in the construction industry, one of whom is a precast concrete slab. In fact, products of innovation are not necessarily fully able to provide a positive impact, both in terms of cost, quality, time, and waste on building construction projects. Moreover, what is offered by the manufacturer of precast concrete slab has not necessarily correspond with the needs of the customer. The purpose of this study is to analyze the comparison of products in terms of time, cost, quality, and waste between projects using precast concrete slab and the same projects that were simulated using floordeck concrete slab. This research will: (1) simulate the project if not using precast concrete slab product, (2) analyze the comparison of products in terms of time, cost, quality, and waste between the real project and the simulation project, (3) calculate the benefits obtained from the use of precast concrete slab product. The use of flyslab at Pertamina Parking Building Project (which consists of three floors and two floors using flyslab) when compared with the results of the simulation project that uses floordeck concrete slab: (1) in terms of time, it can provide a savings of 12.5% of the total duration of the simulation project, (2) in terms of costs, it can provide costs savings on the total cost structure reaches 23.13%, (3) in terms of quality, flyslab constituent materials are designed to have a higher quality when compared to floordeck concrete slab constituent materials, (4) in terms of waste, on a project that uses flyslab, the amount of waste generated is much less when compared to the results of the simulation project that uses a floordeck concrete slab.